Metode Active Learning Type Card Sort dalam Meningkatkan Prestasi Siswa - Ida Rosyidah; Teti Fitriyani (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2020)
The purpose of this research is to find out: 1) the reality of the application of active learning type card sort methods on subjects aqidah morals, 2) the reality of students 'cognitive learning achievement after applying active learning type card sort methods, 3) the effect of applying the active learning type card sort methods to students' cognitive learning achievement. The method used in this research is quasi experimental nonequivalent control group design. Data collection techniques used were observation, test, interview, and documentation study. The results of this study were the percentage of student activity at 78% and teacher activity at 22%. ognitive learning achievement has an average of 87.84 which is categorized very well, and the average using the lecture method is 80.63 which is a moderate category. nalysis of the normality test data showed Xcount 2.02 ≤ Xtable 7.82 with normal distribution. Homogeneity test data analysis that is Fcount = 1.46 ≤ Ftable = 3.32 means the data shows homogeneous. The results of the analysis of the T-test data showed that Tcount = 12.86> Ttable = 2.04 means that H1 was accepted, then there was an influence of the learning process using active learning type card sort method on students' cognitive learning achievement in the subject of aqidah akhlak. AbstrakTujuan diadakannya penelitian ini adalah untuk mengetahui: 1) realitas penerapan metode active learning type card sort pada mata pelajaran aqidah akhlak, 2) realitas prestasi belajar kognitif siswa setelah diterapkan metode active learning type card sort, 3) pengaruh penerapan metode active learning type card sort terhadap prestasi belajar koginitif siswa. Metode yang digunakan dalam penelitian ini adalah quasi eksperiment nonequivalent control group design. Teknik pengumpulan data yang digunakan adalah observasi, test, wawancara, dan studi dokumentasi. Hasil dari penelitian ini adalah Persentasi aktivitas siswa yaitu 78% dan aktivitas guru sebesar 22%. Prestasi belajar kognitif memiliki rata-rata sebesar 87,84 yang berkategori sangat baik, dan rata-rata yang menggunakan metode ceramah sebesar 80,63 yakni berkategori sedang. Analisis data uji normalitas menunjukan Xhitung 2,02 ≤ Xtabel 7,82 berdistribusi normal. Analisis data uji homogenitas yaitu Fhitung = 1,46 ≤ Ftabel = 3,32 artinya data menunjukan homogen. Hasil analisis data Uji T menunjukan Thitung = 12,86 > Ttabel = 2,04 artinya H1 diterima, maka terdapat pengaruh dari proses pembelajaran dengan menggunakan metode active learning type card sort terhadap prestasi belajar kognitif siswa pada mata pelajaran aqidah akhlak.